2001
DOI: 10.1128/jcm.39.5.1999-2001.2001
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus Genotypes P[4]G9, P[6]G9, and P[8]G9 in Hospitalized Children with Acute Gastroenteritis in Rio de Janeiro, Brazil

Abstract: Fifty-three rotavirus-positive fecal specimens from children with diarrhea admitted to a Rio de Janeiro, Brazil, children's hospital between January 1997 and December 1998 were characterized for P and G types by using reverse transcription-PCR. Genotype P[4]G2 accounted for 21% of isolates, while uncommon genotypes P[8]G9, P[6]G9, and P[4]G9 accounted for 13% of the isolates

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
86
0
4

Year Published

2002
2002
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(102 citation statements)
references
References 23 publications
12
86
0
4
Order By: Relevance
“…Our data show the presence of RV-A G1P [8] and G9P [8], confirming that these two genotypes are those more frequently associated with RV-A illnesses worldwide (30)(31)(32)(33). In the city of Salvador, Most worldwide studies have shown that genotype HAstV-1 is the most prevalent, followed by HAstV genotype-2, -3, -4, and -5 (35)(36)(37)(38).…”
Section: Discussionsupporting
confidence: 70%
“…Our data show the presence of RV-A G1P [8] and G9P [8], confirming that these two genotypes are those more frequently associated with RV-A illnesses worldwide (30)(31)(32)(33). In the city of Salvador, Most worldwide studies have shown that genotype HAstV-1 is the most prevalent, followed by HAstV genotype-2, -3, -4, and -5 (35)(36)(37)(38).…”
Section: Discussionsupporting
confidence: 70%
“…Beginning in the mid-1990s, there was a remarkable increase in the detection of G9 strains as a cause of gastroenteritis and over the last 7 years or so, G9 rotaviruses have emerged as one of the most epidemiologically important strains worldwide in both developed and developing countries (Ramachandran et al, 1996;Griffin et al, 2000;Iturriza-Gó mara et al, 2000;Palombo et al, 2000;Widdowson et al, 2000;Araú jo et al, 2001;Bányai et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Some of these may only have local significance (e.g. G5 in parts of Brazil and G8 in Malawi; Bok et al, 2001b;Cunliffe et al, 2001b), but at least one serotype, G9, was demonstrated to have dispersed worldwide (Ramachandran et al, 1996;Unicomb et al, 1999;Griffin et al, 2000;Iturriza-Gó mara et al, 2000;Palombo et al, 2000;Araú jo et al, 2001;Bok et al, 2001a;Cunliffe et al, 2001a;Bányai et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The scheme described above was intended to detect VP7 genotypes G1, G2, G3, G4, G5, G6, G8, G9, G10 and G11. The first round of P genotyping was performed by amplification of the VP8* portion of the VP4 gene, and the second round of amplification was performed with a pool of specific primers for the following P genotypes: P [1], P [4], P [5], P [6], P [7], P [8], P [9], P [10] and P [11].…”
Section: Methodsmentioning
confidence: 99%